To My Love - Cupido, (Saga Egmont, 2021)
Sexy spice for established partners at home, in day-to-day life and escaping from work, house and kids. This is a collection of erotic short stories from Cupido.The collection contains the following \"She quickly pulled up his zipper and wiped her mouth. When the saleswoman came around the corner, she was sitting on the edge of the bed like an innocent schoolgirl, her legs crossed and her hands folded.\" - Warmth by Cecilia, Rogaland\"She had an exam soon, but the books just kept slipping out of her hands. A different hand job required her attention.\" - To My Love by -Mia\"They set up the camera in the living room. That was when she understood why men like to look at women\'s pussies from behind.\" - Mirror, Mirror by Frederico, Stockholm\"Mum and dad try to have a private moment before the kids wake up. It\'s certainly not easy.\" - Tickle Fight by Ild, Oslo\"She pretends to be still asleep, pressed against him, sticks her ass out a little.\"